A composição do fator competências no modelo da internacional de serviços públicos (ISP) de avaliação de postos de trabalho: análise da adequação em Sistema de Remuneração do Serviço Público Municipal Brasileiro - Rodrigues, Haline Cordeiro (2011)
The study provides a comparative discussion between the analytical aspects of treatment and meaning of the Public Services International (PSI) and the contributions of Boterf Le (2003) regarding the parameters of competence as a potential present and needed the job and/or Tour Working in the Public Sector as well as element in evaluating the value of a compensation system. The work is divided into five chapters covering theoretical discussions related to the concept of competence, remuneration in the Public Service, gender equity and gift ideas on the concept of professionalism. It was also the evaluation of positions at the municipal level as a method of designing the pay system. Aimed to broadly examine the composition of the factor defined in Skills Assessment Model Workstations proposed by PSI, in view of its suitability for the system of remuneration of the public service in Brazil, based on the Job and Career Plan of Education of the City of Quixadá (CE). Methodological procedures were established as quantitative and qualitatively in order to support the review of the literature, the single case study concerning the evaluation process made by the Committee Bipartite Equity Compensation (municipal government and union), as well as field research. The application forms interview took place on the server side of the Municipal Department of Education, occupants of 8 (eight) positions effective administrative agent, assistant general services, municipal guard, conductor, driver, teacher education (high school and higher) and supervisor of education. He is the focus on the level of agreement of occupants in relation to the score received by his office in each sub-factor (education and experience, analysis and reasoning abilities, interpersonal skills and physical prowess) Skills Factor Model ISP. The research demonstrated the applicability of the evaluation of jobs in municipal government, as well as realizing that professionalism can provide theoretical support to the discussion of structure in the Public Service positions. They point to research as a restriction lawlessness municipal salary structure defined from the results obtained by scoring positions. Future work may involve other factors besides posts evaluative skills, such as effort, responsibility and working conditions.